Drill wear monitoring using instantaneous angular speed : a comparison with conventional technologies used in drill monitoring systems - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2013)
Dissertation (MEng)--University of Pretoria, 2012.